Clinical features of dopamine agonist withdrawal syndrome in a movement disorders clinic. Issue 2 (29th August 2012) - Pondal, Margarita; Marras, Connie; Miyasaki, Janis; Moro, Elena; Armstrong, Melissa J; Strafella, Antonio P; Shah, Binit B; Fox, Susan; Prashanth, L K; Phielipp, Nicolas; Lang, Anthony E
Abstract : Background: Recently, symptoms similar to addictive drug withdrawal have been reported in a structured longitudinal study of patients with idiopathic Parkinson's Disease (PD) withdrawing from dopamine agonists (DA): the dopamine agonist withdrawal syndrome (DAWS). Objectives: The objective of this study was to establish the frequency, predictors, and outcomes of DAWS in a movement disorders clinic. Methods: We conducted a retrospective chart review of a sample of patients with a clinical diagnosis of PD treated with DA in whom withdrawal or attempted withdrawal of DA was carried out because of adverse effects, or for any other reason. Out of 487 PD patient charts reviewed, 84 were withdrawn from the agonists and were evaluable. Results: Thirteen patients (15.5%) met criteria for DAWS (DAWS+) and 71 did not (DAWS−). DAWS developed upon withdrawal from pergolide, pramipexole and ropinirole, and did not respond to levodopa. DAWS outcomes included recovery in less than 6 months in 61%, in more than a year in 23%, and an inability to discontinue DA in 15% of patients. Development of impulse control disorders was the reason for DA withdrawal in all DAWS+, but only in 41% of DAWS− patients (p<0.0001). DAWS+ and DAWS− patients did not differ in other variables. Conclusion: DAWS is a disabling complication of DA use. Critical features of the syndrome are the strong link with impulse control disorders, possibly the independence of DA dosage and type, and the resistance to treatment, including levodopa. Further studies are required to characterise those at risk as well as to define an effective treatment.